PRAKTIK AKUNTABILITAS KINERJA PADA DIREKTORAT JENDERAL PERHUBUNGAN UDARA REPUBLIK INDONESIA TAHUN 2023 - Bernadus Satya Graha; Dewi Casmiwati (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to analyze the implementation of performance accountability at the Direktorat Jenderal Perhubungan Udara (DJPU) ) of the Ministry of Transportation of the Republic of Indonesia based on the 2023 Government Agency Performance Accountability Report (LAKIP). Performance accountability is a key instrument for assessing public sector organizations’ ability to account for the achievement of strategic objectives and public service quality. This research employs a qualitative approach using a documentary study method. The primary data source is the 2023 LAKIP of the Directorate General of Civil Aviation obtained from the official institutional website. Data were analyzed using content analysis to examine the alignment between performance targets and achievements as well as reported accountability practices. The results indicate that the overall performance of the Directorate General of Civil Aviation in 2023 was categorized as very good, with an average performance achievement of 101.82 percent. Aviation safety and security indicators showed very high achievement, while public service quality was reflected in the user satisfaction index and on time performance exceeding the targets. However, the air transportation connectivity ratio did not fully meet the target, indicating structural and operational challenges. The study concludes that performance accountability at the Directorate General of Civil Aviation has been implemented effectively, although continuous improvement is required, particularly in enhancing air transportation connectivity.